Fruit seeds as sources of bioactive compounds: Sustainable production of high value-added ingredients from by-products within circular economy - Marina Fidelis; Cristiane de Moura; Tufy Kabbas Junior; Nora Pap; Pirjo Mattila; Sari Mäkinen; Predrag Putnik; Danijela Bursać Kovačević; Ye Tian; Baoru Yang; Daniel Granato (M D P I AG, 2022)
The circular economy is an umbrella concept that applies different mechanisms aiming to
minimize waste generation, thus decoupling economic growth from natural resources. Each year,
an estimated one-third of all food produced is wasted; this is equivalent to 1.3 billion tons of food,
which is worth around US$1 trillion or even $2.6 trillion when social and economic costs are
included. In the fruit and vegetable sector, 45% of the total produced amount is lost in the
production (post-harvest, processing, and distribution) and consumption chains. Therefore, it is
necessary to find new technological and environmentally friendly solutions to utilize fruit wastes
as new raw materials to develop and scale up the production of high value-added products and
ingredients. Considering that the production and consumption of fruits has increased in the last
years and following the need to find the sustainable use of different fruit side streams, this work
aimed to describe the chemical composition and bioactivity of different fruit seeds consumed
worldwide. A comprehensive focus is given on the extraction techniques of water-soluble and
lipophilic compounds and in vitro/in vivo functionalities, and the link between chemical composition
and observed activity is holistically explained.